COVID-19 pandemic and worldwide organ transplantation: a population-based study. (October 2021) - Aubert, Olivier; Yoo, Daniel; Zielinski, Dina; Cozzi, Emanuele; Cardillo, Massimo; Dürr, Michael; Domínguez-Gil, Beatriz; Coll, Elisabeth; Da Silva, Margarida Ivo; Sallinen, Ville; Lemström, Karl; Midtvedt, Karsten; et al.
Summary: Background: Preliminary data suggest that COVID-19 has reduced access to solid organ transplantation. However, the global consequences of the COVID-19 pandemic on transplantation rates and the effect on waitlisted patients have not been reported. We aimed to assess the effect of the COVID-19 pandemic on transplantation and investigate if the pandemic was associated with heterogeneous adaptation in terms of organ transplantation, with ensuing consequences for waitlisted patients. Methods: In this population-based, observational, before-and-after study, we collected and validated nationwide cohorts of consecutive kidney, liver, lung, and heart transplants from 22 countries. Data were collected from Jan 1 to Dec 31, 2020, along with data from the same period in 2019. The analysis was done from the onset of the 100th cumulative COVID-19 case through to Dec 31, 2020. We assessed the effect of the pandemic on the worldwide organ transplantation rate and the disparity in transplant numbers within each country. We estimated the number of waitlisted patient life-years lost due to the negative effects of the pandemic. The study is registered with ClinicalTrials.gov, NCT04416256 . Findings: Transplant activity in all countries studied showed an overall decrease during the pandemic. Kidney transplantation was the most affected, followed by lung, liver, and heart. We identified three organ transplant rate patterns, as follows: countries with a sharp decrease in transplantation rate with a low COVID-19-related death rate; countries with a moderate decrease in transplantation rate with a moderate COVID-19-related death rate; and countries with a slight decrease in transplantation rate despite a high COVID-19-related death rate. Temporal trends revealed a marked worldwide reduction in transplant activity during the first 3 months of the pandemic, with losses stabilising after June, 2020, but decreasing again from October to December, 2020. The overall reduction in transplants during the observation time period translated to 48 239 waitlisted patient life-years lost. Interpretation: We quantified the impact of the COVID-19 pandemic on worldwide organ transplantation activity and revealed heterogeneous adaptation in terms of organ transplantation, both at national levels and within countries, with detrimental consequences for waitlisted patients. Understanding how different countries and health-care systems responded to COVID-19-related challenges could facilitate improved pandemic preparedness, notably, how to safely maintain transplant programmes, both with immediate and non-immediate life-saving potential, to prevent loss of patient life-years. Funding: French national research agency (INSERM) ATIP Avenir and Fondation Bettencourt Schueller.